Global patterns of offshore wind variability. Issue 12 (4th May 2021) - West, Chris G.; Smith, Ronald B.
Abstract: Using the 40‐year hourly gridded ERA5 reanalysis, we study the offshore patterns of wind variability using the probability density function (PDF) and the power spectral density (PSD). To summarize wind variability, we compute the Weibull parameters from the PDF and the PSD for six spectral bands: interannual, annual, multimonth, storm, diurnal, and semidiurnal. We characterize the storm spectral peak using a Gaussian function in log 10 frequency space. These parameters are plotted along two pole‐to‐pole transects through the Atlantic Ocean at 25°W and the Pacific Ocean at 170°W longitude and at 16 current and proposed offshore wind sites. We test the idea that coastal and open‐ocean wind statistics may be described by a single set of meridional profiles. In mid‐latitudes, the storm band variance exceeding 20 m 2  s −2 dominates. The Weibull shape parameter is close to k = 2 . The storm interval varies from 4 to 7 days depending on location. In the Northern Hemisphere only, the annual variance is significant, exceeding 3 m 2  s −2 . In the equatorial region, we find steadier winds with small storm variance less than 3 m 2  s −2 . The Weibull shape parameter is k = 4 or greater, suggesting the possibility of a high capacity factor there. The storm interval can exceed 15 days. The equatorial zone has an annual wind variance reaching 2 m 2  s −2, comparable to the storm variance. In the tropical Pacific, we find interannual variance associated with El Niño‐Southern Oscillation (ENSO). Semidiurnal variance is detected in the tropics from the atmospheric tide.